Exploring drivers of energy demand in Cyprus - Scenarios and policy options - Zachariadis, Theodoros; Taibi, Emanuele (My University, 2015)
This paper describes a new set of energy demand forecasts for the Republic of Cyprus up to the year 2040, which have been developed in support of the renewable energy roadmap that was prepared for national authorities by the International Renewable Energy Agency. The analysis takes into account national end-use data from the residential and tertiary sector that had not been exploited up to now. Four final energy demand scenarios with diverging assumptions were defined in this study, offering a wide range of possible outcomes up to 2040; in addition, four alternative scenarios were applied for sensitivity analysis. Two of these scenarios can be regarded as those continuing the trends of the recent past in Cyprus (prior to the economic and financial downturn of years 2011-2014). However, a more rigorous implementation of energy efficiency measures in buildings and transport, as defined in the fourth scenario of this study, is also realistic; despite its potential costs, it might allow Cyprus both to decrease its carbon emissions in line with the long-term EU decarbonisation targets, and to reduce its dependence on fossil fuels, thereby promoting energy efficiency as an important climate change adaptation measure.
Keywords: Decarbonisation; Econometric model; End-use accounting; Energy efficiency action plan; Projections